KREATIVITAS PENGOLAHAN KOLANG-KALING KELOMPOK UKM DUSUN KALIKESEK KECAMATAN LIMBANGAN KABUPATEN KENDAL - Khasanah, Dian Ratu Ayu Uswatun; Ferawati, Eti; Muzammil, Moh.; Pongatung, Ronald Jolly (Universitas Mataram, 2024)
Kalikesek Hamlet is a highland, surrounded by the Ungaran mountain valley which has clear and abundant springs. Kalikesek Hamlet is located under a pine forest where there are quite a lot of sugar palm trees around the village. Due to the large number of palm trees, Kalikesek hamlet is known as Arenan Kalikesek. With so many sugar palm trees, Kalikesek hamlet is a center for producing lots of palm fruit. The abundance of palm fruit has actually become a problem for the local community. The processing of frond frond is still very simple, namely just boiling and soaking, so this fruit frond cannot last long. Most of the soaked palm fruit are only given as feed to livestock. The aim of this service is to assist SMEs in Kalikesek Hamlet, Limbangan District, Kendal Regency in processing fruit and fronds to increase selling value. This service method is carried out in 3 stages, namely preparation, implementation and evaluation. The results of this activity resulted in that palm fruit which previously could only last 3-7 days when processed into packaged drinks could last 3-8 months. Palm fruit which is only used as food for livestock is now processed into products that can have high selling power. With the NHEZ branding, the appearance of kolang kaling drinks is easy for consumers and the market to remember, not just empty packaging without pictures and letters.